Why is Math Difficult? : Beliefs That Affecting Students' Mathematics Skills - Purbaningrum, Mayang; Ramadhan, Sahrul; Thauzahra, Raudya (Jurnal Paedagogy, 2023)
This research aims to describe the factors that influence students' beliefs that mathematics is difficult and how to change students' beliefs that mathematics is not difficult. This research method used a Systematic Literature Review with a qualitative approach. This data was obtained from the thematic analysis of several books and articles discussing 'intelligence", "mathematics," and "mindset" those researchers obtained from Google Scholar. The research results showed that parents, teachers, and peers influence students who think intelligence did not change and could be changed. Apart from that, with a fixed mindset, someone might think that mathematics was difficult because the task given was difficult, assume that if the achievement was low, then mathematics was also low, lack motivation after experiencing failure, and mathematics could not be completed if done for a long period. Parents had the biggest influence on students' mindsets. Genes and socioeconomic background were not the reason. Parental parenting patterns that prioritized performance over process influenced students' thinking patterns. Another biggest influence was the teacher. Like parents, teachers who assess based on performance rather than process would make students lose self-confidence when they fail. Teachers who supported their students to surrender to their situation also made students unmotivated to study mathematics more deeply. Collaboration between teachers, parents, and peers is needed to change a fixed mindset to a growth mindset. Constructive feedback is needed so students are always oriented towards a process without results.